(untitled) - Van Fleet, David D (Australia, 2015)
This comprehensive book approaches agribusiness as a technology-oriented industry composed of organizations ranging in size from small, family-owned farms or businesses to some of the largest corporations in the world. With multiple opportunities for self-review as well as vignettes, cases, and examples in each chapter, this book shows readers the real-world application of what they are learning and provides them with a solid understanding of what management is all about.
Keywords: Ngành nông nghiệp,Agricultural industries,Agricultural industrie,Ngành nông nghiệp; Tài chính,Management,Finance.,Quản lý